Location-Based Advertising: Privacy Concerns No Big Deal - Michael Schade; Rico Piehler; Claudius Warwitz; Christoph Burmann (Marketing Review St.Gallen, 2016)
Location-Based Advertising (LBA) is an innovative advertising channel to deliver highly personalized advertising messages. Based on an empirical study the negative effect of privacy concerns on the intention to use LBA is considerably weaker than the positive effect of advertising value.
Keywords: 650